It Takes a Village: Multidisciplinary Approach to Screening and Prevention of Pediatric Sleep Issues - Jessica R. Sevecke; Tawnya J. Meadows (Medical Sciences, 2018)
Sleep is essential to human development. Poor sleep can have significant effects on cognition, learning and memory, physical and behavioral health, and social-emotional well-being. This paper highlights the prevalence of common pediatric sleep problems and posits that a multidisciplinary approach to the assessment and intervention of sleep problems is ideal. Primary care providers are often the first professionals to discuss sleep issues with youth and families. However, dentists, otolaryngologists, childcare providers, school personnel, and behavioral health providers have a vital role in screening and prevention, providing intervention, and monitoring the progress of daily functioning. The strengths of this approach include better provider-to-provider and provider-to-family communication, streamlined assessment and intervention, earlier identification of sleep issues with more efficient referral, and longer-term monitoring of progress and impact on daily functioning. Barriers to this approach include difficulty initiating and maintaining collaboration among providers, limited provider time to obtain the necessary patient permission to collaborate among all multidisciplinary providers, lack of financial support for consultation and collaboration outside of seeing patients face-to-face, geographic location, and limited resources within communities. Research investigating the utility of this model and the overall impact on pediatric patient sleep issues is warranted and strongly encouraged.